2018
DOI: 10.1108/mip-05-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Examining consumer-brand relationships on social media platforms

Abstract: Purpose The purpose of this paper is to examine how consumer-brand relationships affect brand loyalty and word of mouth when mediated by brand trust considering online brand communities on social media platforms. Design/methodology/approach A conceptual model is developed, depicting the impact of customer-brand relationships on brand loyalty and word of mouth via brand trust. The conceptual model is validated using partial least squares structural equation modeling and data for which are collected online thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 81 publications
4
94
0
5
Order By: Relevance
“…In the online context, previous studies have identified the importance of brand trust as one of the most important direct conditions for loyalty [52,53]. Particularly in that context, where consumers are more uncertain in their interactions, trust in the brand becomes an essential concept for understanding long-term relations [78] and, therefore, loyalty [65,79] between the parties involved in the exchange processes. Consequently, the following hypothesis is proposed: Hypothesis 10 (H10).…”
Section: Brand Loyaltymentioning
confidence: 99%
“…In the online context, previous studies have identified the importance of brand trust as one of the most important direct conditions for loyalty [52,53]. Particularly in that context, where consumers are more uncertain in their interactions, trust in the brand becomes an essential concept for understanding long-term relations [78] and, therefore, loyalty [65,79] between the parties involved in the exchange processes. Consequently, the following hypothesis is proposed: Hypothesis 10 (H10).…”
Section: Brand Loyaltymentioning
confidence: 99%
“…Relationship marketing has been shown to generate strong customer relationships that enhance customer satisfaction, customer loyalty, and firm profits (Firdaus and Kanyan, 2014). It stresses the importance of continuous interactions between the seller and buyer in order to develop a long-term relationship (Jain, Kamboj, Kumar and Rahman, 2018;Palmatier, Dant, Grewal, and Evans, 2006). Additionally, the increasing interest in online shopping has prompted many companies to move into cyberspace (Jensen and Wagner, 2018;Thaichon, 2017).…”
Section: Overviewmentioning
confidence: 99%
“…Relationship marketing is a well-researched area in the domain of consumer research. It involves the development of strong relationships between exchange partners that enhance satisfaction, trust, value, commitment, and loyalty and ultimately improve profitability (Jain et al, 2018; Palmatier et al, 2006; Weaven et al, 2017). Although there is increasing research in consumer or business management acceptance of new technologies (Barnes & Cumby, 2002; Song et al, 2012), the impact of technologies on relationship marketing is often not adequately investigated, leading to overstated hypothetical predictions of its future potential (Bilgihan & Bujisic, 2015; Hart et al, 2000).…”
Section: Overviewmentioning
confidence: 99%